Critical Thinking and Historical Understanding in History Learning: A Systematic Literature Review and Bibliometric Analysis - Jufri, Muhammad Junaldi; Darini, Ririn; Budiman, M; Kinanti, Amalia Nurma; Aolafasila, Ines Zilma; Darmawan, Tengku Hamid (FKIP Universitas Lampung, 2025)
Critical Thinking and Historical Understanding in History Learning: A Systematic Literature Review and Bibliometric Analysis. Objective: This study systematically reviews global research on critical thinking and historical understanding in history education from January 2021 to November 2025. Method: The study employed a Systematic Literature Review (SLR) approach with the PRISMA protocol to answer three research questions. Data were searched in the Scopus database using keywords related to history education and critical thinking. Article selection was carried out using inclusion and exclusion criteria assisted by Covidence, resulting in 21 articles for analysis. The analysis was conducted using bibliometrics (VOSviewer), limited meta-analysis, N-Gain analysis, and narrative synthesis. Result: The study shows an increasing trend toward quantitative methods, quasi-experiments, and Research and Development (R&D), with the largest contribution coming from Indonesia. VOSviewer visualization revealed three main clusters, namely history learning, historical thinking, and critical thinking. The learning strategies used included textbook analysis, the STEM approach, Problem-Based Learning, Project-Based Learning, Peter Seixas' historical thinking framework, and History Work Camp integrated with technology such as Padlet, digital comics, virtual field trips, cloud-based learning, and interactive digital media. A limited meta-analysis showed positive but statistically unstable effects. In contrast, N-Gain analysis showed an increase in historical understanding in the moderate to high categories, especially in authentic experience-based learning and digital technology. Conclusion: This review comprehensively maps the conceptual relationship between history learning, historical thinking, and critical thinking. The main gaps lie in the limited number of stable experimental studies, the lack of instrument standardization, and the dominance of short-term, outcome-oriented designs. Therefore, further research should focus on more rigorous experimental designs, performance-based assessments, longitudinal studies, and the development of integrated learning models grounded in inquiry, reflection, and authentic experience. Keywords: critical thinking, historical understanding, learning strategies, history education, systematic review.